2012
DOI: 10.2967/jnumed.111.095794
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-Labeled Tricarbonyl His-CNA35 as an Imaging Agent for the Detection of Tumor Vasculature

Abstract: Given the importance of angiogenesis for a tumor's survival and growth, several therapeutic strategies rely on the selective inhibition of angiogenesis and the destruction of existing tumor vasculature. These strategies raise the need for a noninvasive tool to evaluate tumor vasculature. We describe the radiosynthesis and evaluation of an imaging tracer that specifically binds tumor subendothelial collagen and thereby images tumor vasculature. Methods: 99m Tc-tricarbonyl was prepared and labeled with His-colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…The preparation of 99m Tc-EG2-C4bpα was performed using tricarbonyl kits and the entire labeling process was completed within two hours. Notably, we achieved labeling yields of 30.3-50.4%, which were similar to those obtained in other studies using the same method, with previously reported yields of 55-65% [23] and 40-50% [24]. We also demonstrated that 99m Tc-EG2-C4bpα was stable in both serum and PBS, and possessed radiochemical purity of more than 90% for up to 24 h post-generation.…”
Section: Discussionsupporting
confidence: 90%
“…The preparation of 99m Tc-EG2-C4bpα was performed using tricarbonyl kits and the entire labeling process was completed within two hours. Notably, we achieved labeling yields of 30.3-50.4%, which were similar to those obtained in other studies using the same method, with previously reported yields of 55-65% [23] and 40-50% [24]. We also demonstrated that 99m Tc-EG2-C4bpα was stable in both serum and PBS, and possessed radiochemical purity of more than 90% for up to 24 h post-generation.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies demonstrated unchanged glucose uptake by inflammatory activation of macrophages (IFN-γ alone or in combination with TNF-α, IL-1β) (13). Others showed enhanced glucose uptake by classic (combination of TNF-α, IL-1β, IFN-γ, and granulocyte macrophage colony-stimulating factor), but not alternative (IL-4 and IL-13), macrophage polarization (36) and increased glucose uptake by both M1 (cotreatment with IFN-γ and LPS) and M2 (IL-4) polarized macrophages (37). Different sources of macrophages (i.e., human monocyte–derived macrophages in the first (13) and murine bone marrow–derived macrophages in the latter 2 studies (3638)) and the use of different polarization agents may have contributed to these conflicting data.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated good stability of [ 99m Tc(CO) 3 ] + :His-tagged protein complex, with minimal transchelation or loss of bound activity, by challenging with high concentrations of histidine and cysteine or incubating in serum [12,14,16,17]. Our group has recently shown that the complex specifically binds to the His-tag, demonstrated by the fact that rhenium tricarbonyl labelled His-tag protein post-tryptic digest is only bound to peptide fragments containing a His-tag [12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we recently demonstrated that the engineered cysteine that increases radiolabelling efficiency is also involved in the coordination of the rhenium tricarbonyl [13]. Several variants on labelling conditions have been studied to optimise the use of [ 99m Tc(CO) 3 ] + -labelling of His-tagged proteins, and there is a general agreement in the literature that labelling at neutral pH, high protein concentration and high temperature increase the rate of radiolabelling (see Additional file 1: Table S1) [1,2,12,14-26]. These conditions, however, exclude proteins that are susceptible to aggregation or loss of function at high temperatures and concentrations or require particularly high specific activity [15,23,25].…”
Section: Introductionmentioning
confidence: 99%